2013
DOI: 10.1063/1.4829875
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the creation yield of shallow single defects in diamond by surface plasma treatment

Abstract: Articles you may be interested inCreation of quantum entanglement with two separate diamond nitrogen vacancy centers coupled to a photonic molecule

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 25 publications
5
38
0
Order By: Relevance
“…The fluorine F1s peak appears at 685 eV and it is shifted by 3 eV compared to the position of the CF 4 treated samples. 20 We do not observe any oxygen peak, expected at around 532 eV, suggesting a good fluorine surface coverage. Nevertheless, from our data we cannot directly conclude that there is a fluorine monolayer on the surface.…”
Section: Plasma Treatmentmentioning
confidence: 59%
See 2 more Smart Citations
“…The fluorine F1s peak appears at 685 eV and it is shifted by 3 eV compared to the position of the CF 4 treated samples. 20 We do not observe any oxygen peak, expected at around 532 eV, suggesting a good fluorine surface coverage. Nevertheless, from our data we cannot directly conclude that there is a fluorine monolayer on the surface.…”
Section: Plasma Treatmentmentioning
confidence: 59%
“…In our previous work 20 and in a related work, 21 it has been shown that very shallow (<5 nm) implanted NVs are stabilized if the diamond surface is treated with oxygen or CF 4 plasma. Here we report a similar effect, namely, NVs produced during the CVD process and close to the surface are not stable neither if the samples are measured directly after the growth nor after boiling them in the three acid mixture.…”
Section: Plasma Treatmentmentioning
confidence: 85%
See 1 more Smart Citation
“…28 The prevailing approach is to keep the implantation energy low (< 5 keV). [24][25][26][27] It is also preferred to set the implantation dose (fluence) low (∼10 8 cm −2 ), so that single NV centers can be resolved optically. On the other hand, standard, multi-purpose ion implantation systems operate at 10 keV or higher with the dose of 10 11 cm −3 or higher, making this approach not widely available.…”
mentioning
confidence: 99%
“…Recent developments in materials fabrication [24,57], ion implantation [58,59], and coherent control techniques [60,61] have brought diamond magnetometers close to the threshold of single nuclear spin sensitivity. These quantum sensors have the potential to be an important tool in proteomics, as they overcome some of the challenges plaguing other experimental techniques, such as x-ray diffraction and conventional NMR.…”
Section: Discussionmentioning
confidence: 99%